The Influence of Leadership and Work Environment on Work Motivation and Its Impact on Employee Performance at the Culture, Tourism, Youth and Sports Service of Dharmasraya Regency - ., Yusradi; Heryanto, (Archives of Business Research, 2019)
This study tries to examine the influence of leadership, work environment and work motivation on employee performance in the Department of Culture, Tourism, Youth and Sports of Dharmasraya Regency. This study uses descriptive quantitative methods. The study population consisted of 50 people from employees. To obtain a valid and realistic instrument, the validity and reliability test, normality test, multicollinearity test and heterocedasticity test were tested. The data analysis technique used is linear regression analysis, t test, f test, determination coefficient, and path analysis using the SPSS program, with α = 0.05. The results showed that the work environment and work motivation had a partially significant effect on the performance of the Department of Culture, Tourism, Youth and Sports Staff in Dharmasraya Regency. leadership, work environment and work motivation partially have a significant effect on the performance of the staff of the Department of Culture, Tourism, Youth and Sports in Dharmasraya Regency. Leadership as an intervening variable has a significant effect between work environment and work motivation on the performance of the staff of the Department of Culture, Tourism, Youth and Sports in Dharmasraya Regency. The empirical findings indicate that to improve community satisfaction, the Dharmasraya District Office of Culture, Tourism, Youth and Sports needs to pay attention and focus more on improving employee performance.